Should I bend or should I grow: the mechanisms of droplet-mediated autophagosome formation. Issue 4 (3rd April 2021) - Schultz, Sebastian W.; Agudo-Canalejo, Jaime; Chino, Haruka; Migliano, Simona M.; Saito, Chieko; Koyama-Honda, Ikuko; Stenmark, Harald; Brech, Andreas; Mizushima, Noboru; Knorr, Roland L.; May, Alexander I.
ABSTRACT: Phase-separated droplets with liquid-like properties can be degraded by macroautophagy/autophagy, but the mechanism underlying this degradation is poorly understood. We have recently derived a physical model to investigate the interaction between autophagic membranes and such droplets, uncovering that intrinsic wetting interactions underlie droplet-membrane contacts. We found that the competition between droplet surface tension and the increasing tendency of growing membrane sheets to bend determines whether a droplet is completely engulfed or isolated in a piecemeal fashion, a process we term fluidophagy. Intriguingly, we found that another critical parameter of droplet-membrane interactions, the spontaneous curvature of the membrane, determines whether the droplet is degraded by autophagy or – counterintuitively – serves as a platform from which autophagic membranes expand into the cytosol. We also discovered that the interaction of membrane-associated LC3 with the LC3-interacting region (LIR) found in the autophagic cargo receptor protein SQSTM1/p62 and many other autophagy-related proteins influences the preferred bending directionality of forming autophagosomes in living cells. Our study provides a physical account of how droplet-membrane wetting underpins the structure and fate of forming autophagosomes.